2019
DOI: 10.4103/jfmpc.jfmpc_243_18
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical markers and lipid profile in nonalcoholic fatty liver disease patients in the PERSIAN Guilan cohort study (PGCS), Iran

Abstract: Background and Aim: Nonalcoholic fatty liver disease (NAFLD) is a global epidemic that is often asymptomatic and silent, and progresses slowly. This study aimed to determine the biochemical markers and lipid profile among NAFLD patients and their possible relationship with degrees of fatty liver. Methods: This is analytical cross-sectional study, in which, 950 individuals referred to the PERSIAN Guilan cohort study were included through sequential sampling method. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 20 publications
(34 reference statements)
2
27
0
Order By: Relevance
“…Dyslipidemia is known as a risk factor for NAFLD, and several studies confirmed that in NAFLD patients, there is a relationship between steatosis degree and lipid profile [ 7 , 8 , 9 , 10 ]. Therefore, it is of crucial importance to assess the effect of an intervention on lipidic parameters, and in this study, Group A patients showed a significant improvement of lipid parameters, with reduction of TC, C-LDL and TG, and an increase of HDL-C levels, with a potential effect also in the cardiovascular outcomes of such patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dyslipidemia is known as a risk factor for NAFLD, and several studies confirmed that in NAFLD patients, there is a relationship between steatosis degree and lipid profile [ 7 , 8 , 9 , 10 ]. Therefore, it is of crucial importance to assess the effect of an intervention on lipidic parameters, and in this study, Group A patients showed a significant improvement of lipid parameters, with reduction of TC, C-LDL and TG, and an increase of HDL-C levels, with a potential effect also in the cardiovascular outcomes of such patients.…”
Section: Discussionmentioning
confidence: 99%
“…In daily clinical practice, measurement of above-mentioned liver enzymes is often associated with the blood lipid profile and insulin resistance measurement, which are used to evaluate and diagnose NAFLD. Several studies confirm that serum biomarkers, such as triglycerides, total cholesterol and low-density lipoprotein (LDL) cholesterol, correlate with NAFLD severity [ 4 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, early diagnosis of NAFLD may be important to prevent these disorders. Diagnostic approaches for detection of NAFLD include serum liver enzyme measurement, imaging analysis such as sonography and magnetic resonance imagining (MRI) and liver biopsy (8). The last one is the gold standard for diagnosis of NAFLD, but this method is invasive and expensive and lots of subjects with suspected NAFLD are reluctant to use it as a diagnostic approach.…”
Section: Introductionmentioning
confidence: 99%
“…There is a paradoxical situation in NAFLD, especially in the context of T2DM. IR results in a reduced ability to inhibit gluconeogenesis, but insulin driven lipogenesis still occurs and is even enhanced [19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Nafld and Metsmentioning
confidence: 99%
“…However, in those patients who have NAFLD, insulin role is diminished. Because of that there is an increase in serum triglycerides levels as well as decrease in HDL levels [31]. Proposed mechanism of pathophysiology regarding the MetS and steatosis development are shown in Figure 1.…”
Section: Nafld and Metsmentioning
confidence: 99%